1994
DOI: 10.1590/s0102-311x1994000400005
|View full text |Cite
|
Sign up to set email alerts
|

Tentativa de controle da leishmaniose tegumentar americana por meio do tratamento dos cães doentes

Abstract: Em área endêmica de leishmaniose tegumentar no Município de Santa Leopoldina, Espírito Santo, foi realizada uma tentativa de controle da endemia por meio do tratamento dos cães doentes. Como controle foi utilizada uma área com características semelhantes no Município de Afonso Cláudio, onde os cães permaneceram sem tratamento. A avaliação inicial revelou que 34 (24%) dos 141 moradores da primeira área eram reatores ao teste intradérmico de Montenegro; entre os cães, 8 (30,7%), dos 26 existentes, apresentavam l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
11
0
4
Order By: Relevance
“…Sessa et al (1994) surveyed residents of the area using the Montenegro skin test, which revealed that 29% were positive for Leishmania infection. The authors carried out this survey among individuals who lived below 700 m and no cases of leishmaniasis have been reported above this altitude since then.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sessa et al (1994) surveyed residents of the area using the Montenegro skin test, which revealed that 29% were positive for Leishmania infection. The authors carried out this survey among individuals who lived below 700 m and no cases of leishmaniasis have been reported above this altitude since then.…”
Section: Discussionmentioning
confidence: 99%
“…Sessa et al (1994) noted that in Liberdade, a village in this municipality, most transmission of the disease was in the peridomicile of houses situated between 600-750 m asl and none occurred above 850 m. Falqueto (1995) collected five man-biting species of sand flies in the village, i.e., Lu. intermedia, Lu.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A presença de cães infectados em áreas endêmicas de leishmaniose tegumentar tem sido investigada, considerando seu papel como reservatório na cadeia de transmissão de Leishmania sp. nos ambientes domiciliar e peridomiciliar (Falqueto et al, 1986;Barreto et al, 1984;Coutinho et al, 1985;Sessa et al,1994). Na região Noroeste do Estado do Paraná, Lonardoni et al (1993) registraram a presença de cães infectados por Leishmania (Viannia) braziliensis.…”
Section: Discussionunclassified
“…No Brasil a presença de cães infectados por Leishmania sp. tem sido freqüente em áreas endêmicas (Dias et al, 1977;Falqueto et al, 1986;Marzochi et al, 1988;Sessa et al, 1994). Na região Noroeste do Estado do Paraná, também foi constatada a presença de cães infectados .…”
Section: Introductionunclassified